2018
DOI: 10.1111/jsr.12687
|View full text |Cite
|
Sign up to set email alerts
|

The reliability of the Epworth Sleepiness Score in a sleep clinic population

Abstract: Despite the Epworth Sleepiness Score being widely used, there are limited studies of its reliability in clinical practice. The aim of this study was to assess the reliability of the Epworth Sleepiness Score in a clinical population. The study included patients referred to Middlemore Hospital sleep service between October and November 2014, aged over 17 years, with at least two Epworth Sleepiness Score measurements at up to three different points on the diagnostic pathway: on General Practitioner referral (GP E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(32 citation statements)
references
References 17 publications
3
28
1
Order By: Relevance
“…Another limit is that several epidemiological studies conducted in clinical settings showed poor test−retest reliability of the ESS (Campbell, Neill, & Scott, 2018;Nguyen et al, 2006;Taylor, Zeng, & O'Dochartaigh, 2019). However, these studies had some weaknesses as the investigators had no control or knowledge on how the ESS were taken, and the study populations included individuals of different ethnicities with potential comprehension difficulties due to poor English language (Campbell et al, 2018;Taylor et al, 2019).…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…Another limit is that several epidemiological studies conducted in clinical settings showed poor test−retest reliability of the ESS (Campbell, Neill, & Scott, 2018;Nguyen et al, 2006;Taylor, Zeng, & O'Dochartaigh, 2019). However, these studies had some weaknesses as the investigators had no control or knowledge on how the ESS were taken, and the study populations included individuals of different ethnicities with potential comprehension difficulties due to poor English language (Campbell et al, 2018;Taylor et al, 2019).…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…As was also noted in our study, the perception of sleepiness when scoring ESS does not correlate with AHI. The retrospective analysis of patients with sleeping disorders by Lee et al also compared the variability of ESS scores at two time points [ 20 ]. They proposed that the ESS should not be used in clinical practice for assessing individual changes or prioritizing patients for diagnostic sleep disorder procedures.…”
Section: Discussionmentioning
confidence: 99%
“…Other methods, such as a naïve correlation analysis, are not sensitive to systematic differences in repeated measures. The present analysis evaluated data from prospective clinical trials, whereas most other studies retrospectively analysed data from chart reviews in clinical practice (Campbell et al, 2018;Lee et al, 2020;Nguyen et al, 2006;Taylor et al, 2019;Walker et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The test-retest reliability of the ESS has primarily been investigated in healthy, community-based samples (Ahmed et al, 2014;Johns, 1992;Knutson et al, 2006). A few studies (Campbell et al, 2018;Lee et al, 2020;Nguyen et al, 2006;Rozgonyi et al, 2021;Taylor et al, 2019;Walker et al, 2020) pants with EDS associated with narcolepsy or OSA, ESS scores were included as a primary or co-primary outcome measure (Malhotra et al, 2020;Schweitzer et al, 2019;Thorpy et al, 2019). The large sample sizes and structured nature of these studies provided an opportunity to assess the test-retest reliability of the ESS in a clinical sample in a clinical trial setting.…”
Section: Introductionmentioning
confidence: 99%